Remote magnetic navigation for catheter ablation of atrioventricular nodal reentrant tachycardia: a systematic review and meta-analysis. (July 2013) - Shurrab, Mohammed; Danon, Asaf; Crystal, Alexander; Arouny, Banafsheh; Tiong, Irving; Lashevsky, Ilan; Newman, David; Crystal, Eugene
Catheter ablation has become a well-established, first-line therapy for atrioventricular nodal reentrant tachycardia (AVNRT), the most common reentry supraventricular tachycardia in humans. Robotic systems are becoming increasingly common in both complex and simple ablation procedures with presumed potential improvements in procedural efficacy and safety. The authors of this article conducted a systematic review and meta-analysis on the effectiveness and safety of the magnetic navigation system (MNS) in comparison with conventional catheter navigation for AVNRT ablation. An electronic search was performed using Cochrane Central database, Medline, Embase and Web of Knowledge between 2002 and 2012. References were searched manually. Outcomes of interest were: acute and long-term success, complications, total procedure, ablation and fluoroscopic times. Continuous variables were reported as standardized difference in means (SDM); odds ratios (OR) were reported for dichotomous variables. Thirteen studies (seven of which were nonrandomized controlled, four were case series and two were randomized controlled studies) involving 679 adult patients were identified. Twelve studies were based on a single center and one study was multicentral. MNS was deployed in 339 patients. The follow-up period ranged between 75 and 180 days. Acute success and long-term freedom from arrhythmia were not significantly different between MNS and control groups (98 vs 98%, OR: 0.94 [95% CI: 0.21–4.1] and 97 vs 96%, OR: 1.18 [95% CI: 0.35–4.0], respectively). A shorter fluoroscopic time was achieved with MNS; however, this did not reach statistical significance (15 vs 19 min, SDM: -0.26 [95% CI: -0.64–0.12]). Longer total procedure but similar ablation times were noted with MNS (160 vs 148 min, SDM: 3.48 [95% CI: 0.75–6.21] and 4 vs 6 min, SDM: -0.83 [95% CI: -2.19–0.53], respectively). The overall complication rate was similar between both groups (2.7 vs 1.0%, OR: 1.28 [95% CI: 0.33–4.96]). Our data suggest that the usage of MNS results in similar rates of success and complications when compared with conventional manual catheter ablation for AVNRT. MNS had a trend for reduced fluoroscopic time. Longer total procedure time was observed with MNS while the actual ablation time remained similar. Prospective randomized trials will be needed to better evaluate the relative role of MNS for catheter ablation of AVNRT.